2008
DOI: 10.1097/mlg.0b013e318161e56b
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Peak Nasal Inspiratory Flow and Rhinomanometry in Functional Rhinosurgery

Abstract: RMM and PNIF provide valuable information to support clinical decision making. However, with both methods, approximately 25% of symptomatic patients with functionally relevant nasal structural deformity were not detected. A negative test outcome of RMM or PNIF does not exclude a functionally relevant nasal stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
1
17

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 14 publications
(18 reference statements)
1
94
1
17
Order By: Relevance
“…PNIF has been widely used in studies aimed at the assessment of nasal airflow, especially in allergic rhinitis patients. The studies found in the literature address data on sensibility, diagnosis accuracy, reproducibility, and reference values of the instrument (8)(9)(10)(11)16,17,21,22) . Our sample showed higher prevalence of mouth-breathing patients in the age group of 6-10 years (Table 1), in agreement with findings of the literature (23,24) -even though some studies have not identified differences concerning age (7,19) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PNIF has been widely used in studies aimed at the assessment of nasal airflow, especially in allergic rhinitis patients. The studies found in the literature address data on sensibility, diagnosis accuracy, reproducibility, and reference values of the instrument (8)(9)(10)(11)16,17,21,22) . Our sample showed higher prevalence of mouth-breathing patients in the age group of 6-10 years (Table 1), in agreement with findings of the literature (23,24) -even though some studies have not identified differences concerning age (7,19) .…”
Section: Discussionmentioning
confidence: 99%
“…Patients were briefly oriented about how to use the instrument; they were supposed to stand up, put on the face mask, covering the regions of the mouth and nose, breathe out and then breathe in at their utmost. We performed three measures and considered the highest value for the analysis (9)(10)(11)(12)16,17) . Data were analyzed using the SPSS statistical program, with significance level set at 5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vascular characteristics of the submucosa provide the inferior concha with the feature of an erectile tissue, and the contracting or dilating venous sinusoids and arteriovenous anastomoses affect the nasal passage airflow (1,19,20). Nasal decongestants agents reduce concha volume and cause an increase in nasal airflow by causing vasoconstriction in these vascular elements (18).…”
Section: Discussionmentioning
confidence: 99%
“…A redução da resistência nasal após uso do vasoconstritor (Tabela 4) ocorreu em intensidade próxima às relatadas na literatura, a saber 43% (105) , 29% (100) e 34% (77) . Isto sugere que a vasoconstrição foi adequada e, portanto, o efeito do ciclo nasal e da posição corporal na resistência nasal foi evitado (78,79) .…”
Section: Efeito Do Vasoconstritorunclassified